Dose–response association of Chinese visceral adiposity index with comorbidity of hypertension and diabetes mellitus among elderly people - Ren, Yongcheng; Cheng, Lulu; Qie, Ranran; Han, Minghui; Kong, Lingzhen; Yan, Wei; Li, Zheng; Li, Yiduo; Lei, Yicun (Frontiers in Endocrinology, 2023)
Background: Chinese visceral adiposity index (CVAI) is a reliable indicator of visceral obesity, but little is known about the association of CVAI with comorbidity of hypertension (HTN) and diabetes mellitus (DM). This study aimed to explore the associations of CVAI with HTN-DM comorbidity, HTN or DM, HTN, and DM in elder people and evaluate the mediating role of insulin resistance in the associations. Methods: A total of 3,316 Chinese participants aged ≥60 years were included in this cross-sectional study. Logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Restricted cubic splines were applied to explore the dose–response associations. Mediation analyses were used to assess mediating effect of triglyceride-glucose (TyG) index in the associations. Results: The prevalence rate of HTN-DM comorbidity, HTN or DM, HTN, and DM was 13.78%, 72.26%, 67.16%, and 18.88%, respectively. Linear associations between CVAI and HTN-DM comorbidity, HTN or DM, HTN, and DM were found, and ORs (95%CIs) were 1.45 (1.30-1.61), 1.39 (1.28-1.52), 1.36 (1.25-1.48), and 1.28 (1.16-1.41) for per SD increase in CVAI. Compared with quartile 1 of CVAI, risk of HTN-DM comorbidity, HTN or DM, HTN, and DM increased 190%, 125%, 112%, and 96% for quartile 4. Besides, we found TyG index playing a key role in the associations of CVAI with HTN-DM comorbidity, HTN or DM, and DM. Conclusions: CVAI is linearly and positively correlated with HTN-DM comorbidity, HTN or DM, HTN, and DM. The potential mechanism is insulin resistance largely mediating the associations.